Mindreading in Infancy. (1st April 2013) - Carruthers, Peter
Abstract Various dichotomies have been proposed to characterize the nature and development of human mindreading capacities, especially in light of recent evidence of mindreading in infants aged 7 to 18 months. This article will examine these suggestions, arguing that none is currently supported by the evidence. Rather, the data support a modular account of the domain‐specific component of basic mindreading capacities. This core component is present in infants from a very young age and does not alter fundamentally thereafter. What alters with development are the interactions between core mindreading and other systems, including executive systems, and forms of learning that do not require radical conceptual change.